Source code-based context-sensitive dynamic slicing of web applications. (21st October 2019) - Singh, Jagannath; Mohapatra, Durga Prashad
Web applications are broadly utilised for spreading business around the globe. To meet the necessities of the huge numbers of users or customers, the web applications must have better quality and robustness than any other applications where the number of users is limited. Program slicing is found to be useful in improving program understanding, analysis, testing and maintenance. This paper presents a context-sensitive slicing technique for web applications. In this paper, a new intermediate representation called web dependence graph (WDG) is proposed for representing all dependencies that may present in a web application. We have proposed a context-sensitive web slicing (CSWS) algorithm for computation of slices of a given web application using the WDG. A tool is developed for automatic generation of the WDG for a given web application and computation of slices. During our literature survey, we noticed that majority of the automatic graph generation tools are mainly based on byte-code whereas our tool uses the dependency analysis from the source code of the given program. Using our tool WDG, we compared the performance of our proposed CSWS algorithm for slicing with other closely related slicing techniques.